2020
DOI: 10.3390/mi11020215
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic-Based Biosensor for Blood Viscosity and Erythrocyte Sedimentation Rate Using Disposable Fluid Delivery System

Abstract: To quantify the variation of red blood cells (RBCs) or plasma proteins in blood samples effectively, it is necessary to measure blood viscosity and erythrocyte sedimentation rate (ESR) simultaneously. Conventional microfluidic measurement methods require two syringe pumps to control flow rates of both fluids. In this study, instead of two syringe pumps, two air-compressed syringes (ACSs) are newly adopted for delivering blood samples and reference fluid into a T-shaped microfluidic channel. Under fluid deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…However, it tended to decrease after t = t 6 . According to previous experimental results obtained with the micro-PIV technique [41], hematocrit had a strong influence on blood velocity obtained with micro-PIV. In this study, it was impossible to obtain information on the hematocrit of blood flow over time.…”
Section: Quantification Of Interface (β) and Intensity (I B ) As Preliminary Studysupporting
confidence: 56%
See 1 more Smart Citation
“…However, it tended to decrease after t = t 6 . According to previous experimental results obtained with the micro-PIV technique [41], hematocrit had a strong influence on blood velocity obtained with micro-PIV. In this study, it was impossible to obtain information on the hematocrit of blood flow over time.…”
Section: Quantification Of Interface (β) and Intensity (I B ) As Preliminary Studysupporting
confidence: 56%
“…French et al demonstrated that the flow rate of suspension blood (RBCs in 1× PBS, hematocrit [Hct] = 10-20%) could be quantified with the micro-PIV technique [40]. The blood flow rate obtained with micro-PIV is varied significantly depending on the hematocrit [41]. For example, when aggregation-enhanced blood is circulated in an in vitro loop, the hematocrit of blood is varied continuously over time [30].…”
Section: Introductionmentioning
confidence: 99%
“…This study was primarily aimed at minimizing the blood volume suctioned in the driving syringe. In previous studies, RBC sedimentation has been tested under different conditions, including suction blood volume (40–200 μL, 41 0.2 mL, 17,33 0.3 mL, 45 0.6 mL, 35 1 mL, 16,32,36 and 4–10 mL 56,62 ), and test reservoir (straight tube, 21,28 disposable syringe, 36 polycarbonate cartridge, 41 conical tube 17,33 ). A considerable blood volume (∼1 mL) was injected into the blood syringe to monitor RBC sedimentation in a driving syringe pump.…”
Section: Resultsmentioning
confidence: 99%
“…Then, blood viscosity was determined using a parallel co-flowing method with a correction factor. The author was able to measure blood viscosity and the RBCs' sedimentation rates consistently for samples with hematocrit 30%, 40% and 50% [7].…”
mentioning
confidence: 97%
“…Kang [7] presented a microfluidic-based biosensor for the measurement of blood viscosity and red blood cells' (RBCs') sedimentation rates. The author used two aircompressed syringes to deliver blood samples and a reference fluid into a T-shaped microfluidic channel and measured the average velocity of the fluids using micro-particle image velocimetry and digital image processing.…”
mentioning
confidence: 99%